Modified Microneedle for Suprachoroidal Injection of Triamcinolone Acetonide Combined with Intravitreal Injection of Ranibizumab in Branch Retinal Vein Occlusion Patients - Nawar AE (Clinical Ophthalmology, 2022)
Amin E Nawar Ophthalmology Department, Faculty of Medicine, Tanta University, Tanta, EgyptCorrespondence: Amin E Nawar, Ophthalmology Department, Faculty of Medicine, Tanta University, Tanta, 31516, Egypt, Tel +20 1140095692, Email nawar20012002@gmail.comPurpose: The present study evaluated the efficacy of combined suprachoroidal injection of triamcinolone acetonide (TA) using a modified microneedle with intravitreal injection of ranibizumab in branch retinal vein occlusion (BRVO) patients.Patients and methods: This is a prospective randomised interventional study that was conducted on 60 eyes of 60 patients with non ischemic BRVO. Patients were divided in two groups, group (1) 30 patients who received intravitreal injection of 0.05 mL (0.5 mg) of ranibizumab, group (2) included 30 patients who received baseline combined intravitreal injection of 0.05 mL (0.5 mg) of ranibizumab and suprachoroidal injection of triamcinolone acetonide (4mg/0.1mL), both groups received monthly injection of ranibizumab on pro-re-nata (PRN) regimen for 1 year duration of the study.Results: Group 2 received less number of injections (2.47 ± 1.2) as compared to group 1 (4.4 ± 1.5). Both groups achieved significant reduction of central macular thickness (CMT) after 12 months of injection with p value < 0.001. Both groups showed significant improvement of best corrected visual acuity (BCVA) after 12 months with p value < 0.001. Group 2 showed more significant improvement of BCVA after 6 and 12 months. The baseline CMT and the number of injections were the main predictors of the final BCVA in group 1, while the baseline BCVA was the only predictor of final BCVA in group 2.Conclusion: Combined suprachoroidal injection of TA using this modified microneedle with intravitreal injection of ranibizumab resulted in more significant improvement of BCVA and reduction of CMT compared with ranibizumab monotherapy with no reported ocular or systemic side effects. The study was prospectively registered with clinical trial.gov ID (NCT04690608) in 27-12-2020.Keywords: branch retinal vein occlusion, suprachoroidal injection, triamcinolone acetonide